A Meta-Analytical Review of the Genetic and Environmental Correlations between Reading and Attention-Deficit/Hyperactivity Disorder Symptoms and Reading and Math. (2nd January 2020) - Daucourt, Mia C.; Erbeli, Florina; Little, Callie W.; Haughbrook, Rasheda; Hart, Sara A.
ABSTRACT: According to the Multiple Deficit Model, comorbidity results when the genetic and environmental risk factors that increase the liability for a disorder are domain-general. In order to explore the role of domain-general etiological risk factors in the co-occurrence of learning-related difficulties, the current meta-analysis compiled 38 studies of third- through ninth-grade children to estimate the average genetic, shared environmental, and nonshared environmental correlations between reading and attention-deficit/hyperactivity disorder (ADHD) symptoms, and reading and math, as well as their potential moderators. Results revealed average genetic, shared and nonshared environmental correlations between reading and ADHD symptoms of .42, .64, and .20, and reading and math of .71, .90, and .56, suggesting that reading and math may have more domain-general risk factors than reading and ADHD symptoms. A number of significant sources of heterogeneity were also found and discussed. These results have important implications for both intervention and classification of learning disabilities.